PENGGUNAAN MEDIA ANIMASI AUDIO VISUAL DALAM PEMBELAJARAN MENYIMAK CERITA ANAK - ANTARA, PUTU ADITYA (JURNAL PENDIDIKAN ANAK USIA DINI, 2012)
This study aims to determine the childs listening skills and learn the story model of learning listening skills animated childrens story through audio visual media in third grade primary school students of Islam at Taqwa, Rawamangun. This research method in the form of a qualitative case study approach.This study found in a personal voice teachers in the classroom is small, too fast to read the story, is not appropriate intonation, facial expressions do not fit with the story, do not pay attention to student responses. In addition, the lack of learning can also be seen from the environment such as the students sit too far away from the teacher, no media / visual aids, and students are not cooperative learning strengths while listening to stories of children who carried out the teacher can be seen from the preparation of teachers teaching has prepared the administrative preparations, the stages are done listening to the teacher is like a stage to hear, understand, interpret, evaluate, and respond has been done well, as well as other advantages of these teachers have done an evaluation at the end of the learning process.Keywords: audi animated visual media, children listen to stories